Multidetector computed tomographic urography for evaluation of vascular and ureteric anomalies associated with ectopic kidneys - M. Y., Gagandeep; M., Gautam; G., Abhinaya; N., Sindhu (International Journal of Research in Medical Sciences, 2022)
Background: The purpose of this study is to evaluate the vascular and ureteric anomalies associated with ectopic kidneys with multidetector computed tomography (MDCT). Methods: The 40 patients with pre-diagnosed ectopic kidney undergoing MDCT urography (Contrast study) and KUB (Plain study) were included in this cross-sectional observational study. The location and number of bilateral kidneys were assessed. The number and origin of the renal arteries and renal veins were noted. Their relationship with each other and possible complications in surgical handling analysed. Data collected was analysed using descriptive and inferential statistics. Results: The renal artery originated from suprarenal aorta in 2 cases, normal origin in 10 cases, infrarenal aorta in 12 cases, aortic bifurcation in 19 cases, common iliac artery in 6 cases and iliac artery bifurcation in 2 cases. The renal vein was of normal origin in 8 cases, originated from infrarenal inferior vena cava (IVC) in 16 cases, IVC bifurcation in 14 cases, common iliac vein in 9 cases, internal iliac vein in 2 cases and external iliac vein in 1 case. There was a significant correlation between the level of ectopic kidneys (abdominal, iliac and pelvis) and level of origin of arteries (p<0.001) and veins (p<0.001). In addition, significant correlation was found between the origins of arteries and veins of ectopic kidneys (p<0.001). Conclusions: A knowledge of the possible variations in renal vasculature and ureter associated with ectopic kidneys can play a key role in preventing iatrogenic hemorrhage during surgery.